Modelado y simulación de un sistema automático de adquisición de datos en centrales hidroeléctricas pequeñas - Freire Piedra, Santiago Ismael (2015)
This paper has developed a measurement system by means of facilities and potential that gives us the computer and microcontroller obtaining study records of interest to know the behavior of the different parameters of electric power. Analysis and validation of results obtained through simulations existing software like Matlab and LabVIEW, creating patterns that in reality are presented today in the production of electricity will take place. Specifically, it has posed a data acquisition system for monitoring electrical parameters in small hydropower using the PIC18F452 microcontroller. The development environment will be characterized in Labview in conjunction with automated validation system with Matlab. Research will develop a design of a Data Acquisition System for the measurement and monitoring of electrical parameters in a min-hydro. Using a microcontroller that allows the development of an automated system that allows better handling of the variables and their transmission to a PC, increasing the facilities and services for control and supervision. In developing this work a characterization of data acquisition systems using the Microcontroller PIC18F452 be made by exploiting the RS232 serial communication system. It is noteworthy that the parameters studied are ideal values, as it is monitoring the magnitudes a central delivery to transform mechanical energy into electricity, without charge.